2013
DOI: 10.1177/0022034513507452
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrients and Oral Clefts

Abstract: Little is known about oral clefts in developing countries. We aimed to identify micronutrientrelated and environmental risk factors for oral clefts in Thailand. We tested hypotheses that maternal exposure during the periconceptional period to multivitamins or liver consumption would decrease cleft lip with or without cleft palate (CL ± P) risk and that menstrual regulation supplements would increase CL ± P risk. We conducted a multisite hospital-based case-control study in Thailand. We enrolled cases with CL ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…Some studies suggest low zinc concentrations may increase oral cleft risk, although associations may vary by place (Krapels et al, ; Tamura et al, ; Munger et al, ). In a recently published study conducted in Thailand, we found that low intake of liver increased oral cleft risk (McKinney et al, ). The only other study to examine liver intake, conducted in Denmark, found no association between liver intake and oral cleft risk but reported that those with the highest levels of vitamin A estimated from liver intake and supplement use combined had a decreased risk of cleft lip with or without cleft palate (CL±P) (Mitchell et al, ).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Some studies suggest low zinc concentrations may increase oral cleft risk, although associations may vary by place (Krapels et al, ; Tamura et al, ; Munger et al, ). In a recently published study conducted in Thailand, we found that low intake of liver increased oral cleft risk (McKinney et al, ). The only other study to examine liver intake, conducted in Denmark, found no association between liver intake and oral cleft risk but reported that those with the highest levels of vitamin A estimated from liver intake and supplement use combined had a decreased risk of cleft lip with or without cleft palate (CL±P) (Mitchell et al, ).…”
Section: Introductionmentioning
confidence: 82%
“…Non‐nutritional environmental risk factors are also implicated. For example, in our recently published case–control study in Thailand, we found that menstrual regulation supplements, which may contain alcohol or herbs with estrogenic effects, increase oral cleft risk (McKinney et al, ). Environmental or passive smoke exposure may increase oral cleft risk, but it is difficult to separate out the effects of maternal smoke exposure from other sources of smoke exposure (Li et al, ).…”
Section: Introductionmentioning
confidence: 98%
“…A more recent study on the Thai population confirmed the existence of a positive correlation between the intake of multivitamins and the reduced risk of cleft defects. The same effect is observed with meals containing liver, while the intake of menstrual cycle regulators by the mother was associated with an increased risk of offspring born with birth defects [11]. According to some studies, the occurrence of diseases like cold and fever in early pregnancy may also contribute to the formation of cleft anomaly [12].…”
mentioning
confidence: 71%
“…The relationship between micronutrients and orofacial clefts was examined by C.M. McKinney among the Thai population and women who reported taking a folic acid supplement in the preconception period were 0.51 times as likely to have an affected child than those who did not, although this finding was not statistically significant (P= 0.12) [26]. All included studies characteristics are listed in table 1 .…”
Section: Figure1 Flow Chart For Studies Selectionmentioning
confidence: 99%